3D relativistic hydrodynamic computations using lattice-QCD-inspired equations of state - Hama, Yogiro; Andrade, Rone P. G.; Grassi, Frederique; Socolowski, Otavio; Kodama, Takeshi; Tavares, Bernardo; Padula, Sandra S. (Elsevier B.V., 2006)
In this communication, we report results of three-dimensional hydrodynamic computations, by using equations of state with a critical end Point as suggested by the lattice QCD. Some of the results are an increase of the multiplicity in the mid-rapidity region and a larger elliptic-flow parameter nu(2). We discuss also the effcts of the initial-condition fluctuations and the continuous emission.